2003
DOI: 10.1021/jf030004y
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Quality Control, and Antimicrobial Activity of the Essential Oil of Long-Time Stored Dill (Anethum graveolens L.) Seeds from Bulgaria

Abstract: The essential oil of long-time stored seeds of dill (Anethum graveolens L.) from Bulgaria was analyzed by physicochemical methods, gas chromatography (GC), GC-mass spectrometry (MS) (achiral and chiral phases), and olfactometry, and its antimicrobial activity was tested by using different strains of microorganisms. More than 40 constituents of the essential dill oil, obtained from seeds stored for more than 35 years, could be identified as essential volatiles, responsible for the pleasant fresh (D-limonene) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 19 publications
6
50
0
2
Order By: Relevance
“…The results obtained from the analysis are in good agreement with the previous reported work [11][12][13]. It has been previously reported that during the developmental growth of seeds, the conversion of dillapiole to oxygenated terpenes increases [14].…”
Section: Chemical Investigationssupporting
confidence: 91%
“…The results obtained from the analysis are in good agreement with the previous reported work [11][12][13]. It has been previously reported that during the developmental growth of seeds, the conversion of dillapiole to oxygenated terpenes increases [14].…”
Section: Chemical Investigationssupporting
confidence: 91%
“…Jirovetz et al (2003) reported a high activity of the essential A. graveolens oil against the mold Aspergillus niger and the yeasts Saccharomyces cerevisiae and Candida albicans. In antifungal investigations, Singh et al (2006) found that the dill essential oil was highly effective for controlling the growth of Penicillium citrinum and Aspergillus niger.…”
Section: Resultsmentioning
confidence: 99%
“…This may give an indication that C. aegyptiaca is a limonene-rich plant, compared with some other plants. For instance, essential oil of dill seeds was reported to be 9.34% [46]; and (44.1% or 16.6% or 16.0%) in Anethum graveolens seeds; according to results published by other investigators [47][48][49]. But citrus limonene exceeded these levels, and was reported to range between 51.97% in Sour Orange oil and 95.32% in Lime oil [36].…”
Section: Discussionmentioning
confidence: 99%